2019
DOI: 10.3390/antiox8110507
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Physical Exercise and Spirulina maxima Supplementation Improve Body Composition, Cardiorespiratory Fitness, and Blood Lipid Profile: Correlations of a Randomized Double-Blind Controlled Trial

Abstract: Cardiovascular diseases are part of the highly preventable chronic diseases associated with changes in lifestyle. Within them, physical activity, low-fat and high-fiber diets are distinguished as the main support for prevention, even when supplementation with nutraceuticals has become a very common practice. Fifty-two young sedentary men with excess body weight (body mass index (BMI) ≥ 25 kg·m−2) were enrolled in a randomized-crossover controlled trial [six weeks of a systematic physical exercise with Spirulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…When it was given in association with physical activity, the best outcome was achieved [ 216 ]. A similar study also showed that spirulina in association with physical activity can improve significantly cardiorespiratory fitness more than a single intervention alone [ 217 ]. A meta-analysis on the spirulina impact on plasma lipid concentration confirmed what was already known.…”
Section: Nutraceuticals In Atherosclerosismentioning
confidence: 99%
“…When it was given in association with physical activity, the best outcome was achieved [ 216 ]. A similar study also showed that spirulina in association with physical activity can improve significantly cardiorespiratory fitness more than a single intervention alone [ 217 ]. A meta-analysis on the spirulina impact on plasma lipid concentration confirmed what was already known.…”
Section: Nutraceuticals In Atherosclerosismentioning
confidence: 99%
“…According to Henry [ 2 ], the idea around functional foods follows the oriental philosophy that established “medicine and food have a common origin” [ 2 ]. In this context, when associated with a balanced diet and physical activity, functional foods’ consumption could be linked to beneficial health effects [ 3 , 4 ]. It includes their ability to reduce heart disease risk, mitigate neurodegenerative diseases, and prevent metabolic disorders such as type 2 diabetes mellitus (T2DM) [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Los estudios sobre la actividad física y el perfil metabólico muestran que el ejercicio físico regular puede resultar en una disminución de la concentración de colesterol total y triglicéridos y un aumento de HDL en individuos con dislipidemia (McKinney et al, 2016;Nassef, Nfor, Lee, Chou, & Liaw, 2019). Además, una dieta equilibrada asociada con el ejercicio mejoró la concentración de glucosa en la sangre en ayunas y la concentración general de lípidos (Hernández-Lepe et al, 2019;Kawano et al, 2009;McKinney et al, 2016;Ooi & Ridzuan, 2016). Estos estudios también señalan que la intensidad del ejercicio puede ser un factor importante para estas modificaciones (He & Wang, 2019;Wood, Murrell, van der Touw, & Smart, 2019).…”
Section: Discussionunclassified